(untitled) (Fiep Bulletin - online, 2019)
The purpose of this paper is present a brief discussion about the representations of the female body,emphasizing the heroines of the comics, especially the Wonder Woman. This question is fundamental to understanding therepresentative changes of the female body over time, drawing attention to the masculine aspect of the female beauty body fromAncient Greece, spanning through Ancient Rome, the Middle Ages, Renaissance and Enlightenment, still, the nineteenth centuryand the impact of the industrial revolution on the conceptions of body. In the twentieth century and the threshold of the twenty-firstcentury the taxation processes of certain female body patterns is linked to the perspective of the cultural industry, inauguratedespecially with the advent of television media in the mid-twentieth century. From the methodological point of view, thebibliographical research on feminine corporeity, the studies on the woman-wonder in the HQ’s. In addition, we seek to analyze therole of physical education in the process of elaborating methods in order to respond to the perspectives of modeling the femalebody conceived by the cultural industry.